PENGARUH FLEXIBLE WORK DAN WORK ENGAGEMENT TERHADAP JOB SATISFACTION DENGAN PERFORMANCE SEBAGAI MEDIASI - Adam Sasando; Primadia Putri Harmastuti; Ahmad Muzakir Bin Ahmad Faizal (Universitas Duta Bangsa Surakarta, 2025)
This study aims to analyze the influence of flexible work, work engagement, and performance on job satisfaction, and to test the mediating role of performance in the relationship between flexible work and job satisfaction in generation Z in Semarang City. The approach used is quantitative with the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that work flexibility has a positive and significant effect on performance and job satisfaction. Performance also has a significant effect on job satisfaction, as well as being a significant mediator in the relationship between work flexibility and job satisfaction. However, work engagement does not show a significant effect on job satisfaction. The evaluation model shows that all constructs have validity and reliability criteria, and have adequate predictive ability based on the R-Square and Q-Square values. These findings emphasize the importance of implementing flexible work to improve performance and job satisfaction, especially in generation Z.